Pemanfaatan Bubble Flame Untuk Implementasi Proses Brazing - Setyoko, Adi Tri; Widyanto, Susilo Adi; Haryadi, Gunawan Dwi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
Abstract In the current era of industrialization, welding technology plays a very important role in the manufacturing or metal joining and assembly industry, one of which is brazing. Brazing is the process of joining specimens using metal and filler that melt in the liquid phase, while the base metal used has a melting point above the filler through heat distribution and the use of filler metal. The aim of this research is to investigate the tensile and bending test strength, from the application of the bubling method and to determine the optimal fuel in the brazing process. The connection model in this research is the lap joint type. The results of research on the brazing process using the bubling method obtain a constant temperature output, so that the filler metal can melt evenly. From the bending test and tensile test results data for each specimen using traditional brazing welding and the bubbling method for Pertalite and Pertamax fuels shows varied results. The bending stress experienced a graph of successive decreases, namely 2.92Mpa for Specimen A, 2.92Mpa for Specimen B and 2.57Mpa for Specimen C. However, in contrast to the resulting tensile stress, there was a graph of increase respectively, 20.87Mpa for Specimen A, 21.76Mpa. specimen B and peak with 34.59Mpa for specimen C. Then the optimal fuel which produces optimal combustion in the brazing process using the bubling method is Pertamax.